Morphological changes and ontogenetic development of Amblyseius eharai Amitai & Swirski (Acari: Phytoseiidae) - Li, Dong-Dong; Yi, Tian-Ci; Guo, Jian-Jun; Jin, Dao-Chao (Zootaxa, 2022)
This paper describes the immature and mature characteristics of Amblyseius eharai Amitai & Swirski in detail to determine its morphological ontogeny based on laboratory-reared specimens. The main changes during ontogeny are as follows: the pronotal shield extends to j6 level and opisthosoma is unsclerotized in the larva; the dorsum has two shields in the protonymph, pronotal shield slightly expended comparing to that of the larva, and the opisthonotal shield smooth and weakly sclerotized. The podonotal and opisthonotal shields in the deutonymph are partially fused, and the dorsal shield is complete, covering almost the entire opisthonotum in adults in both sexes. There are nine pairs of dorsal setae in the larva, 14 pairs in the protonymph, and 19 pairs in both deutonymph and adult. In deutonymphs, gender could be distinguished by the number of setae in the area around the anal valves. In protonymphs, all dorsal, hypostomal setae, and the macrosetae of leg IV appear and are consistent with the subsequent stages. The development of morphological traits in the ontogeny of A. eharai may provide some basic knowledge to distinguish it from closely related species.